Ion uptake and distribution in sweet potato genotypes subjected to salt stress is not driven by transpiration - Mondal, S.; Rahaman, E.H.M.S.; Asch, F. (Wiley, 2024)
Potassium is taken up actively by the plant, whereas sodium is often either competing for the same uptake mechanisms or uptake and distribution are driven by the transpirational volume flow in the shoots of plants grown under salinity. Reducing transpiration rate is regarded as an adaptation mechanism to reduce leaf tissue salt load. In combination with a high K uptake, plants may be able to maintain growth and are, thus, seen as salt-tolerant. Little is known about these mechanisms in sweet potato (Ipomoea batatas L.). Therefore, cuttings of two sweet potato genotypes contrasting in salinity tolerance (CIP 188002.1, tolerant; CIP 189151.8, sensitive) were subjected to 0 and 50 mM NaCl root zone salinity in a hydroponic system and grown under low (0.76 kPa) and high (2.27 kPa) vapour pressure deficit (VPD) to create differences in transpiration. After 18 days of initial hydroponic growth, NaCl was added for another 33 days. Cumulative plant water loss and total uptake of Na, K and Cl were determined for all plants and treatments. Transpirational water loss was twice as high under high VPD as compared to low VPD conditions, but genotypic Na and Cl accumulation remained almost the same. In contrast to plants subjected to salt stress under low VPD conditions, genotypes under high VPD conditions differed significantly in transpiration. However, in both genotypes transpirational water loss from individual leaves and Na or Cl accumulation were not correlated, under high VPD younger leaves of CIP 188002.1 (tolerant) accumulated more than twice as much potassium than in CIP 189151.8 (sensitive). The distribution of the three ions across leaf positions and within one leaf position between petiole and leaf blade differed strongly between the two genotypes. Tolerant CIP 188002.1 accumulated up to five times more sodium and potassium in the leaf petioles in the middle-aged and young leaf positions than in the leaf blade, whereas in sensitive CIP 189151.8 neither ion was preferentially accumulated in the petioles. This was independent of salinity treatment and VPD conditions. In contrast, hyperaccumulation of Cl in petioles only occurred under high VPD conditions in the petioles of the tolerant genotype, but not under low VPD conditions, indicating a VPD sensitivity for Cl distribution in sweet potato. While we conclude that transpirational volume flow is not a main driving force for Na and Cl uptake and distribution within the plant, we discuss potential pathways leading to the hyperaccumulation of sodium and potassium in the leaf petioles of the tolerant genotype. We suggest studies on HKT transporter activities in the petioles as an object of further studies in sweet potato.